Kwaba mnyama kukhanya : ukhuvethe lwansondo - Zulu, N. S. (Nogwaja Shadrack), 1959- (Bhiyoza Publishers (Pty) Ltd., 2020)
This book is about short stories and essays which talk about the social impact of Covid-19 and hard lockdown restrictions in South Africa. In iZulu the short stories and essays found in this book introduce us to the evolving and living conditions that people live in during the lockdown. The themes addressed in this book show the ways in which South Africans were affected due to the deplorable social conditions under the strict rules of the lockdown. The major themes addressed in this book, include among others, the challenges faced by the teachers and learners in schools, having to adopt to the new modes of teaching and learning (online teaching) and the issue of government disregarding the cultures, customs, beliefs, and traditions of Black people during the lockdown. The life experienced by the poor Black people is revealed in such a way that each writer writes about the background of the story built under this time of social crisis of the lockdown. Each author created his own place where the events took place in the story he invented and thereafter re-created the characters showing how they got along because of the situation of social pressure.